A randomised controlled trial to investigate the feasibility and acceptability of a small change approach to prevent weight gain. - Graham, Henrietta; Madigan, Claire; Daley, Amanda J. (Journal of Behavioral Medicine, 2024)
A weight gain prevention strategy showing merit is a small change approach (increase energy expenditure and/or decrease energy intake by 100–200 kcal/day). Studies have tested a small change approach in intensive interventions involving multiple contacts, unsuitable for delivery at scale. The aim here was to assess the feasibility and acceptability of a remote small change weight gain prevention intervention. A randomised controlled trial of 122 participants was conducted. The intervention was a remote 12-week small change weight gain prevention programme (targeting dietary and/or physical activity behaviours). The comparator group received a healthy lifestyle leaflet. Data were collected at baseline and 12-weeks. The primary outcome was the feasibility and acceptability, assessed against three stop–go traffic light criteria: retention, number of participants randomised per month and adherence to a small change approach. Participants' opinions of a small change approach and weight change were also measured. The traffic light stop–go criteria results were green for recruitment (122 participants recruited in three months) and retention (91%) and red for intervention adherence. Most participants (62%) found a small change approach helpful for weight management and the mean difference in weight was − 1.1 kg (95% CI − 1.7, − 0.4), favouring the intervention group. Excluding intervention adherence, the trial was feasible and acceptable to participants. Despite adherence being lower than expected, participants found a small change approach useful for weight management and gained less weight than comparators. With refinement to increase intervention adherence, progress to an effectiveness trial is warranted. ISRCTN18309466: 12/04/2022 (retrospectively registered).